The Met1-linked ubiquitin machinery in inflammation and infection - Fiil, BK; Gyrd-Hansen, M; Gyrd-Hansen, M (Springer Nature, 2021)
Ubiquitination is an essential post-translational modification that regulates most cellular processes. The assembly of ubiquitin into polymeric chains by E3 ubiquitin ligases underlies the pleiotropic functions ubiquitin chains regulate. Ubiquitin chains assembled via the N-terminal methionine, termed Met1-linked ubiquitin chains or linear ubiquitin chains, have emerged as essential signalling scaffolds that regulate pro-inflammatory responses, anti-viral interferon responses, cell death and xenophagy of bacterial pathogens downstream of innate immune receptors. Met1-linked ubiquitin chains are exclusively assembled by the linear ubiquitin chain assembly complex, LUBAC, and are disassembled by the deubiquitinases OTULIN and CYLD. Genetic defects that perturb the regulation of Met1-linked ubiquitin chains causes severe immune-related disorders, illustrating their potent signalling capacity. Here, we review the current knowledge about the cellular machinery that conjugates, recognises, and disassembles Met1-linked ubiquitin chains, and discuss the function of this unique posttranslational modification in regulating inflammation, cell death and immunity to pathogens.